Utilization of ischemic preconditioning for athletes competing and training at altitude: applications and perspectives - Billaut, F.; Paradis-Deschênes, P.; Richard, P. T. (Journal of Science in Sport and Exercise, 2022)
Acute exposure to altitude negatively impacts exercise tolerance and reduces athletes` race performance due to lower atmospheric and body tissues oxygen partial pressures. Chronic exposure to altitude has also been used for several decades by athletes to increase training adaptations. However, the decline in arterial oxygen saturation also impacts 'trainability' and athletes are forced to travel to lower altitude for intensified training. For the athlete preparing for altitude, the advantages of properly timed terrestrial acclimatization and/or sea-level hypoxia-based pre-acclimatization recommendations are clear. However, the associated cost, demands, and time investment make these best-practice strategies difficult or impossible to implement for many athletes. This perspective and opinion article summarizes current knowledge on the potency of ischemic preconditioning (i.e., a sequence of transient ischemic episodes followed by reperfusion) to enhance the pulmonary, vascular, and metabolic determinants of performance at altitude with the aim to derive implications to accelerate or facilitate altitude acclimatization for varied goals. We discuss potential applications for athletes and propose innovative questions for future research in this field.